Pengaruh Penggunaan Variasi Jenis Busi Dan Variasi Bahan Bakar Terhadap Emisi Gas Buang HC, CO, CO2 Dan O2 Pada Sepeda Motor Honda Beat FI Tahun 2016 - Deno Maharbudi; Husin Bugis; Ranto Ranto (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
The purpose of this research are (1) Knowing and obtaining the results of the investigation of the effect of variations in spark plug types on exhaust emissions of HC, CO, CO2 and O2 on Beat FI 2016 motorbikes (2) Knowing and obtaining the results of investigating the effect of variations in fuel on exhaust emissions HC, CO, CO2 and O2 on Beat FI 2016 motorbikes (3) Knowing and obtaining the results of the investigation of the effect of spark plug types and fuel variations on exhaust emissions of HC, CO, CO2 and O2 on Beat FI 2016 motorbikesThis research uses descriptive quantitative research with experimental research methods. Measurement of exhaust emissions in accordance with SNI 09-7118.3-2005. The population in this study was a Honda Beat FI motorcycle. The sample in this study was a Honda Beat FI motorbike in 2016. The data collection technique was using purposive sampling. The research was conducted at Dishubkominfo Surakarta city using the gaz analyzer technotest.Results of this research is (1) The use of a combination of pertalite fuels and iridium plugs generates the lowest HC rate of 118.67 ppm or a decrease of 32.58% (2) The use of pertalite fuel with platinum plugs decreases by producing the lowest CO rate of 0.487% or decrease 3.31% (3) pertamax fuel with standard plugs resulted in the lowest CO2 exhaust emission of 10.5% with a difference of 2.27 or decrease 17.75% (4) use of pertalite fuel with standard plugs capable of producing O2 exhaust gas emissions of 1.057% or the lowest.